Pulmonary vascular malformations in genetic epileptic encephalopathy: A rare, fatal case report - N. Garancini; M. Ghezzi; A. Farolfi; V. Guaia; G. Canali; V. Fabiano; G.V. Zuccotti; E. D'Auria (Respiratory Medicine Case Reports)
Mutations of KCNT1 gene, encoding for a sodium-gated potassium channel, are causative of a wide spectrum of epilepsies and neurodevelopmental disorders; cardiovascular involvement also seems to be significant, with cardiac arrhythmia and, less frequently, the development of Systemic to Pulmonary Collateral Arteries (SPCAs) has been reported. We report the case of M., affected by a KCNT1-related drug-resistant epileptic encephalopathy, who presented fatal complications with massive hemoptysis due to SPCAs. We aim to increase the awareness regarding this infrequent but potentially severe clinical condition.